Computational Studies of Coinage Metal Anion M− + CH3X (X = F, Cl, Br, I) Reactions in Gas Phase - Fan Wang; Xiaoyan Ji; Fei Ying; Jiatao Zhang; Chongyang Zhao; Jing Xie (Molecules, 2022)
We characterized the stationary points along the nucleophilic substitution (SN2), oxidative insertion (OI), halogen abstraction (XA), and proton transfer (PT) product channels of M− + CH3X (M = Cu, Ag, Au; X = F, Cl, Br, I) reactions using the CCSD(T)/aug-cc-pVTZ level of theory. In general, the reaction energies follow the order of PT > XA > SN2 > OI. The OI channel that results in oxidative insertion complex [CH3–M–X]− is most exothermic, and can be formed through a front-side attack of M on the C-X bond via a high transition state OxTS or through a SN2-mediated halogen rearrangement path via a much lower transition state invTS. The order of OxTS > invTS is inverted when changing M− to Pd, a d10 metal, because the symmetry of their HOMO orbital is different. The back-side attack SN2 pathway proceeds via typical Walden-inversion transition state that connects to pre- and post-reaction complexes. For X = Cl/Br/I, the invSN2-TS’s are, in general, submerged. The shape of this M− + CH3X SN2 PES is flatter as compared to that of a main-group base like F− + CH3X, whose PES has a double-well shape. When X = Br/I, a linear halogen-bonded complex [CH3−X∙··M]− can be formed as an intermediate upon the front-side attachment of M on the halogen atom X, and it either dissociates to CH3 + MX− through halogen abstraction or bends the C-X-M angle to continue the back-side SN2 path. Natural bond orbital analysis shows a polar covalent M−X bond is formed within oxidative insertion complex [CH3–M–X]−, whereas a noncovalent M–X halogen-bond interaction exists for the [CH3–X∙··M]− complex. This work explores competing channels of the M− + CH3X reaction in the gas phase and the potential energy surface is useful in understanding the dynamic behavior of the title and analogous reactions.